High levels of LDL-C combined with low levels of HDL-C further increase platelet activation in hypercholesterolemic patients - Chan,L.W. (2015)
High levels of low-density lipoprotein cholesterol (LDL-C) enhance platelet activation, whereas high levels of high-density lipoprotein cholesterol (HDL-C) exert a cardioprotective effect. However, the effects on platelet activation of high levels of LDL-C combined with low levels of HDL-C (HLC) have not yet been reported. We aimed to evaluate the platelet activation marker of HLC patients and investigate the antiplatelet effect of atorvastatin on this population. Forty-eight patients with high levels of LDL-C were enrolled. Among these, 23 had HLC and the other 25 had high levels of LDL-C combined with normal levels of HDL-C (HNC). A total of 35 normocholesterolemic (NOMC) volunteers were included as controls. Whole blood flow cytometry and platelet aggregation measurements were performed on all participants to detect the following platelet activation markers: CD62p (P-selectin), PAC-1 (GPIIb/IIIa), and maximal platelet aggregation (MPAG). A daily dose of 20 mg atorvastatin was administered to patients with high levels of LDL-C, and the above assessments were obtained at baseline and after 1 and 2 months of treatment. The expression of platelets CD62p and PAC-1 was increased in HNC patients compared to NOMC volunteers (P<0.01 and P<0.05). Furthermore, the surface expression of platelets CD62p and PAC-1 was greater among HLC patients than among HNC patients (P<0.01 and P<0.05). Although the expression of CD62p and PAC-1 decreased significantly after atorvastatin treatment, it remained higher in the HLC group than in the HNC group (P<0.05 and P=0.116). The reduction of HDL-C further increased platelet activation in patients with high levels of LDL-C. Platelet activation remained higher among HLC patients regardless of atorvastatin treatment.